The call of wild - London, Jack, 1876-1916 ([Boston, Mass] : Thomson Heinle, 2005)
An unusual dog, part St. Bernard, part Scotch shepherd, is forcibly taken to Alaska where he eventually becomes leader of a wolf pack
Title from container
Keywords: Animal welfare -- Fiction; Feral dogs -- Fiction; Pet theft -- Fiction; Dogs -- Fiction